La manifestación de interés en los procesos de menor cuantía, por medio del correo electrónico, debe ser efectiva a nivel Nacional (2019)
The mechanism of abbreviated selection in the processes of smaller amount, as one of the different modalities of selection, according to the current provisions requires the introduction of the requirement called the manifestation of interest in participating, which means that it is the entire manifestation of the will from a bidder to the entity that represents the State to present the offer within a process that is in progress. This expression of interest in participating, is a document in which the most basic data are consigned, such as the name of the proponent, when a natural person, if the legal representative´s name, identification, addreess, telephone number is legal and the email to contact them. A few years ago, many physical writings that resided in the state entity were used, however, with the passage of time and some rules, the use of technological means, including the use of data messages and the use of email, which the latter became a tool that has facilitated expressing this manifestation of interest in participating in those minor processes, as long as geographically in the entity there is such access.